2020
DOI: 10.1109/access.2020.3034032
|View full text |Cite
|
Sign up to set email alerts
|

Explainable Machine Learning for Early Assessment of COVID-19 Risk Prediction in Emergency Departments

Abstract: Between January and October of 2020, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus has infected more than 34 million persons in a worldwide pandemic leading to over one million deaths worldwide (data from the Johns Hopkins University). Since the virus begun to spread, emergency departments were busy with COVID-19 patients for whom a quick decision regarding in-or outpatient care was required. The virus can cause characteristic abnormalities in chest radiographs (CXR), but, due to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 128 publications
0
54
0
4
Order By: Relevance
“…Unfortunately, though a great deal of research work has been devoted to the development of methods for automated COVID-19 diagnosis [ 18 ], severity scoring or prognosis prediction, and outcome prediction [ 8 , 13 ], we are still far from reaching a solution. That is due to the lack of a unified and anonymized, multi-device and multi-ethnicity, appropriately annotated and shareable datasets containing enough samples to ensure a robust model validation against the COVID-19 disease variability.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, though a great deal of research work has been devoted to the development of methods for automated COVID-19 diagnosis [ 18 ], severity scoring or prognosis prediction, and outcome prediction [ 8 , 13 ], we are still far from reaching a solution. That is due to the lack of a unified and anonymized, multi-device and multi-ethnicity, appropriately annotated and shareable datasets containing enough samples to ensure a robust model validation against the COVID-19 disease variability.…”
Section: Related Workmentioning
confidence: 99%
“…In times of crisis, such as the current COVID-19 pandemic, rapid and efficient patient diagnosis and prognosis assessment would highly improve patient care and reduce mortality rate by eliminating the time intervals between Emergency Department (ED) arrival and hospitalization. For a quick and precise patient risk assessment, Computed Tomography (CT) has been described as an important diagnostic tool [ 5 , 6 ], given its capability of reducing RT-PCR false negative results [ 7 ] and its superior sensitivity compared to chest X-ray [ 8 ]. Indeed, CT quantification of pneumonia lesions can timely and non-invasively predict the progression to severe illness [ 9 ], providing a promising prognostic indicator for clinical management of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Additional features of COVID-19, such as pleural/septal thickening, subpleural involvement, and bronchiectasis, can be noticed in the later stages of the disease. It is worth noting that some related works, such as [ 5 , 6 ], suggest the use of chest radiographs (CXR) due to their widespread availability and portability, non-invasiveness, and faster acquisition and visual analysis. However, CTs have higher accuracy than CXR and allow diminishing the false negative errors from repeated swab analysis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The imputations obtained were compared to the 100 imputations computed by missForest, [21][22][23] which applies Random Forests (RF) in a similar way to RF-mice. To choose the best imputation model, as detailed in Casiraghi et al, 24 this study used the Wilcoxon rank-sum test (p-value < 0.05) to statistically compare the between-imputation-variances obtained with increasing imputation runs (from 1 to 100). This showed that missForest was the most stable imputer.…”
mentioning
confidence: 99%
“…Samples below the CXR cut-off point were considered as moderate/mild patients, while those above the CXR cut-point were further analyzed to select the most important variables for a more precise outcome prediction. To this aim, Boruta algorithm 23,[26][27][28][29] used an internal 5-fold crossvalidation as detailed by Casiraghi et al 24 3. Selected variables were used to train an RF, which was then pruned and simplified to create a simple associative tree 30,31 and to finally estimate the importance of the variables.…”
mentioning
confidence: 99%